High temperature and short-term oxidation behavior of CoCrCu1.2FeNi high entropy alloy in solid and semi-solid state. (December 2021) - Huang, Minjie; Jiang, Jufu; Wang, Ying; Liu, Yingze; Zhang, Ying
Abstract: The short-term oxidation behavior of CoCrCu1.2 FeNi high entropy alloy in solid and semi-solid state was investigated. Except for the two-stage parabola characteristic at 1340 ℃, the oxidation kinetics of other temperatures showed single-stage parabola characteristic. The oxidation products and oxide scales were characterized by X-ray diffraction (XRD) and scanning electron microscopy (SEM) with energy dispersion spectrum (EDS). During solid oxidation, the oxide scales were composed of outer oxide layer (CuO and Cu2 O) and inner oxide layer (Co, Cr, Fe, Ni3 O4 ) spinel oxides. During semi-solid oxidation, internal and external diffusion was significantly enhanced, liquid flow and holes became diffusion channels. Graphical Abstract: ga1 Highlights: The oxidation kinetics of CoCrCu1.2 FeNi high entropy alloy in solid and semi-solid were calculated. During solid oxidation, the oxide scales exhibited a double-layer structure. During semi-solid oxidation, the FCC2 phase undergoing intense oxidation. The external diffusion of Cu ions and the inner internal of oxygen during solid oxidation. Internal and external diffusion, liquid flow and holes became diffusion channels during semi-solid oxidation.